Decoloniality and the (im)possibility of an African feminist philosophy. Issue 3 (3rd July 2022) - Griffiths, Dominic
Abstract : This article offers a prolegomenon for an African feminist philosophy. The prompt for this as an interrogation of Oluwele's claim that an African feminist philosophy cannot develop until identifiable African worldviews that guide the relationship between men and women have been established. She argues that until there is general agreement about the nature of African philosophy itself, African feminist philosophy will remain impoverished. I critique this claim, unpacking Oluwele's argument, and examine the contested nature of both African and Western philosophy. Drawing from the work of Mignolo and decolonial thinking, I then argue for the possibility of "epistemic disobedience" concerning the emergence of an African feminist philosophy. Engaging with precolonial African examples which disrupt modern normative gender assumptions and looking at the project of decoloniality, I issue a call for an African feminist philosophy unfettered by the falsely universal claims of modernity/coloniality. My call is for an African feminist philosophy from African loci of enunciation, rooted in the epistemes and experiences of African women. "Most thought-provoking in our thought-provoking time is that we are still not thinking" (Heidegger 1968, 6).